Adherence to Home Physiotherapy Treatment in Children and Young People with Joint Hypermobility: A Qualitative Report of Family Perspectives on Acceptability and Efficacy. (1st July 2013) - Birt, Linda; Pfeil, Michael; MacGregor, Alexander; Armon, Kate; Poland, Fiona
Abstract Objective Joint hypermobility can lead to pain and motor developmental problems in children and young people (CYP). Exercise programmes may help CYP with joint hypermobility strengthen core muscle groups. Non‐ adherence to home physiotherapy is common. The present study aimed to understand how families experienced an intensive multidisciplinary intervention. Method This was a qualitative study nested within a randomized controlled trial of a multidisciplinary treatment intervention, including physiotherapy, for children aged five to 17 years. Twenty‐eight families were recruited following the intervention. Semi‐structured interviews were used to examine the views and expectations of parents and CYP, and examine adherence to the exercise programme. Thematic analysis of data was used to develop findings. Results Parents and CYP reported that exercise reduced the symptoms of hypermobility. Parental motivation, adapting family routines, making exercise a family activity and seeing benefit increased adherence to exercise. Non‐adherence to exercise was linked to lower levels of parental supervision, not understanding the treatment, not seeing benefit and not having specific time to dedicate to doing the exercises. Conclusion Even when exercise is seen to benefit a child's well‐being, families experience challenges in adhering to a physiotherapy programme for hypermobility. Therapists can utilize findings on what enhances adherence to help CYP effectively exercise in the home setting. Copyright © 2013 John Wiley & Sons, Ltd.